Antimicrobial filtration with electrospun poly(vinyl alcohol) nanofibers containing benzyl triethylammonium chloride: Immersion, leaching, toxicity, and filtration tests. (January 2017) - Park, Jeong-Ann; Kim, Song-Bae
Abstract: Antimicrobial electrospun poly(vinyl alcohol) (PVA) nanofibers were synthesized by impregnating benzyl triethylammonium chloride (BTEAC) as an antimicrobial agent into PVA nanofibers. The BTEAC-PVA nanofibers were heat-methanol treated during the preparation for various tests. The BTEAC-PVA nanofibers became more hydrophilic than the PVA nanofibers due to incorporation of BTEAC. Through heat-methanol treatment, thermal property, crystallinity, and water stability of BTEAC-PVA nanofibers were improved considerably. The immersion test shows that heat-methanol treatment has an advantage over heat treatment to maintain BTEAC content in BTEAC-PVA nanofibers. The acute toxicity test demonstrates that the 24-h EC50 and 48-h EC50 values (EC50  = median effective concentration) of BTEAC to Daphnia magna were 113 and 90 mg/L, respectively. The leaching test indicates that the BTEAC concentration leached from BTEAC-PVA nanofibers was far below the concentration affecting the immobilization of D. magna . For antimicrobial filtration tests, the BTEAC-PVA nanofibers were deposited onto glass fiber filter. The antimicrobial filtration test was conducted against bacteria ( Escherichia coli, Staphylococcus aureus ) and bacteriophages (MS2, PhiX174), demonstrating that the BTEAC-PVA nanofibers could enhance the removal of E. coli and S. aureus considerably but not the removal of MS2 and PhiX174 under dynamic flow conditions. Graphical abstract: Image Highlights: Antimicrobial BTEAC-PVA nanofibers were synthesized using electrospinning process. Water stability of BTEAC-PVA nanofibers was improved by heat-methanol treatment. Leached BTEAC was far below the toxicity level for D. magna immobilization. Bacteria removal could be enhanced by incorporation of BTEAC into PVA nanofibers.